In-Service English Teacher’s Lived Experience in Using ChatGPT in Teaching Preparation - Nernere, Regina Putri; Kastuhandani, Fidelis Chosa (SALEE: Study of Applied Linguistics and English Education, 2024)
ChatGPT usage has gained popularity in education. ChatGPT is an AI that can produce human-like text and has implications for education. This study explored eight Indonesian English teachers’ lived experiences in integrating ChatGPT in their teaching preparation. In-service teachers’ perceptions, emotions, pedagogical activities, decision-making, and teaching transformations were explicated from their lived experiences through one-on-one in-depth interviews. The data gathered was later analyzed through transcendental framework analysis. The findings highlighted teachers’ various perceptions. Some considered this AI as a useful tool to generate ideas and materials with the awareness of its limitations in human-like understanding. Further, teachers experienced both excitement and concern towards ChatGPT. The integration practice resulted in improved teaching planning among teachers while retaining the quality after thoughtful adaptations. Additionally, ChatGPT helped teachers provide a better learning approach and contextualized learning. Significantly, as ChatGPT becomes more widely accessible, further research is required to guide teachers on its wiser utilisation.